The Effects of Secondary Oxides on Copper‐Based Catalysts for Green Methanol Synthesis - Hayward, James S. (ChemCatChem, 2017)
Catalysts for methanol synthesis from CO(2) and H(2) have been produced by two main methods: co‐precipitation and supercritical anti‐solvent (SAS) precipitation. These two methods are compared, along with the behaviour of copper supported on Zn, Mg, Mn, and Ce oxides. Although the SAS method produces initially active material with high Cu specific surface area, they appear to be unstable during reaction losing significant amounts of surface area and hence activity. The CuZn catalysts prepared by co‐precipitation, however, showed much greater thermal and reactive stability than the other materials. There appeared to be the usual near‐linear dependence of activity upon Cu specific area, though the initial performance relationship was different from that post‐reaction, after some loss of surface area. The formation of the malachite precursor, as reported before, is important for good activity and stability, whereas if copper oxides are formed during the synthesis and ageing process, then a detrimental effect on these properties is seen.